Determination of the optimum time for preparation of half-boiled eggs free from Salmonella Enterica Serovar Enteritidis / Mohamad Fithri Akmar Omar … [et al.] - Omar, Mohamad Fithri Akmar; Abdul Manaf, Nurdiyana Syahirah; Mohd Sufian, Siti Nurnajwa Nadhirah; Zakaria, Norsuhaida; Ayub, Nur Farhah Najwa; Mohd Nawi, Siti Farah Alwani; Mohd Zain, Zaini (Universiti Teknologi MARA Cawangan Selangor, 2018)
Consuming half-boiled eggs during breakfast is popular among Malaysians. The eggs are usually prepared by submerging them in freshly boiled water for about 20 minutes duration. As chickens have the likelihood of harbouring Salmonella enterica Serovar Enteritidis in their eggs, it is feared that consumption of half-boiled eggs contaminated with S. Enteritidis could lead to gastroenteritis. Hence, this study was carried out to determine the optimum time required for boiled water to kill S. Enteritidis in half-boiled eggs. Methods: Grade C chicken eggs (average weight 54.5 g) were obtained from a local sundry shop and were confirmed to be Salmonella-free prior to the experiment. Fifteen eggs that were previously spiked with 106 colony-forming units (CFU) of S. Enteritidis were completely submerged into freshly-boiled water (≈100ºC) for a maximum of 20 min. Positive controls consisted of eggs that were inoculated but were not treated. At every 5 min interval, three eggs were taken out and checked for presence of viable S. Enteritidis on MacConkey agar, and the respective water temperature was recorded. Results: Results of two independent trials showed that after 10 min of submerging the eggs in the hot water, there were an average of 3 log reductions in the CFU of S. Enteritidis but after 15 min, no viable S. Enteritidis was detected. Conclusion: A half-boiled egg should be prepared by submerging it in freshly boiled water for at least 15 min to ensure that it is safe to be consumed.